2014
DOI: 10.1002/sim.6247
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity adjustments in testing for bioequivalence

Abstract: Bioequivalence of two drugs is usually demonstrated by rejecting two one-sided null hypotheses using the two one-sided tests for pharmacokinetic parameters: area under the concentration-time curve (AUC) and maximum concentration (Cmax). By virtue of the intersection-union test, there is no need for multiplicity adjustment in testing the two one-sided null hypotheses within each parameter. However, the decision rule for bioequivalence often requires equivalence to be achieved simultaneously on both parameters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In this paper, we go beyond such univariate considerations and discuss how bioequivalence can and should be demonstrated for two or more PK parameters simultaneously. The TOST procedure itself is easy to extend by applying the intersection‐union principle, and other multivariate equivalence tests are available as well,() but there have been controversies about how to construct a simultaneous confidence region around the vector of estimated PK measures. A number of ideas have been put forward in the past two decades: Various authors suggested methods tailored to (bio‐)equivalence problems,() but also approaches that were not specifically designed for application in pharmaceutical statistics() may prove useful.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we go beyond such univariate considerations and discuss how bioequivalence can and should be demonstrated for two or more PK parameters simultaneously. The TOST procedure itself is easy to extend by applying the intersection‐union principle, and other multivariate equivalence tests are available as well,() but there have been controversies about how to construct a simultaneous confidence region around the vector of estimated PK measures. A number of ideas have been put forward in the past two decades: Various authors suggested methods tailored to (bio‐)equivalence problems,() but also approaches that were not specifically designed for application in pharmaceutical statistics() may prove useful.…”
Section: Introductionmentioning
confidence: 99%
“…As a further and practical consideration, a multiple testing issue for multiple PK endpoints would be needed in addition to the fixed sequence testing procedure considered between PK and efficacy endpoints because two PK endpoints, that is, AUC and Cmax, are often evaluated in practice in the PK trial. 49 In addition, several types of AUC are often set as primary endpoints. For instance, AUCs from time zero to predicted infinity and from time zero to the last measurable concentration were assessed in addition to Cmax as primary endpoints in the PK study within the development of the biosimilar adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, testing such an expanded family of hypotheses is as good as testing the family with individual hypotheses only. It is worthwhile to mention that similar UI formulation of composite hypotheses is becoming increasingly common in multi-endpoint bioequivalence and non-inferiority studies of drugs (Quan et al 2001; Logan & Tamhane 2008; Hasler & Hothorn 2013; Hua et al 2015). This stems from the need for inference on individual endpoints.…”
Section: Methodsmentioning
confidence: 99%